PENGARUH PARTISIPASI PENGANGGARAN PADA KESENJANGAN ANGGARAN DENGAN KARAKTER PERSONAL SEBAGAI PEMODERASI - Linggar Tanaya, I Gusti Made; Krisnadewi, Komang Ayu (E-Jurnal Akuntansi; Vol 17 No 3 (2016), 2016)
This research aims to get empirical evidence about the effect of participation in budgeting on budgetary slack and personal character as moderating influence on participation in budgeting on budgetary slack in the Department of Klungkung regency. This research was conducted at the Department in Klungkung and using a questionnaire as a survey method. The samples were analyzed by 48 respondents and using purposive sampling as the method of sampling. The analysis technique in this research is Moderated Regression Analysis (MRA). The research proves that participation in budgeting have significant positive effect on the budgetary slack and personal character have significant positive effect on the relationship between participation in budgeting on budgetary slack. It means the higher level of participation in budgeting at the Department of Klungkung regency, the budgetary slack will increase, and if the employee who participated in budgeting process have pessimistic personal character it will increase budgetary slack.
Keywords: participation in budgeting, budgetary slack, personal character